Collective Female Labour Supply : Theory and Application - Olivier Donni (Institute for the Study of Labor (IZA), 2005)
In this paper, we deal with female labour supply in the collective framework. We study married couples and start from the empirical observation that the husband?s labour supply is generally fixed at full-time. We then show that, in this case, structural elements of the decision process, such as individual preferences or the rule that determines the intrahousehold distribution of welfare, can be identified if household demand for at least one commodity, together with the wife?s labour supply, is observed. These theoretical considerations are followed by an empirical application using French data.
Keywords: D12; J22; 330; collective decisions; female labour supply; commodity demands; Frauenerwerbstätigkeit; Arbeitsangebot; Ehe; Haushaltsökonomik; Familienökonomik; Schätzung; Frankreich